2017
DOI: 10.1111/petr.12902
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life after combined liver and kidney transplantation in children

Abstract: While reduced HRQOL following isolated organ transplantation has been previously reported, there are no data in the context of children following CLKT. Twenty-three children who underwent CLKT at our institution were included in the study. The indication for CLKT was PH1 in 13 patients and ARPKD in 10 patients. Quantification of HRQOL was facilitated through the use of the PedsQL 4.0 Generic Core Scale. The results of the study were compared to healthy children and published data of children who had undergone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…One included study, identified in the expanded search, reported on a combined sample of renal transplant and end‐stage renal disease patients . The article was retained as a majority of patients were transplant recipients, and the objective was to evaluate the psychometric properties of two instruments (PedsQL ™ Generic Core Scales and PedsQL ™ End Stage Renal Disease Module) identified in other articles which reported on transplant samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One included study, identified in the expanded search, reported on a combined sample of renal transplant and end‐stage renal disease patients . The article was retained as a majority of patients were transplant recipients, and the objective was to evaluate the psychometric properties of two instruments (PedsQL ™ Generic Core Scales and PedsQL ™ End Stage Renal Disease Module) identified in other articles which reported on transplant samples.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this systematic review show that PROMs are being used in the field of pediatric solid organ transplant . However, researchers advise that both generic and disease‐specific instruments are used to conduct a comprehensive evaluation of health status and overall QOL to generate more accurate depictions of a patient's health‐related QOL .…”
Section: Discussionmentioning
confidence: 99%
“…Health-related quality of life was only examined systematically in a single study [ 26 ], using the PedsQL™ instrument. However, this study of children after combined liver and kidney transplantation did not report results for the ARPKD subgroup (10 of 23 patients) separately.…”
Section: Resultsmentioning
confidence: 99%
“…Longer disease duration and older age in children with CKD were associated with better HRQOL in physical, social, and emotional domains, suggesting that time to adapt may improve HRQOL [9]. Further, levels of HRQOL after a kidney transplant has been mixed, with evidence of an increase in HRQOL across domains through the first year post-transplant [8], as well as findings of lower HRQOL relative to control groups [10].…”
Section: Health-related Quality Of Life Among Pediatric Kidney Transp...mentioning
confidence: 99%
“…Studies of HRQOL in mixed pediatric organ transplant samples (e.g., heart and liver) yield similarly inconsistent findings. Many found that transplant recipients reported lower HRQOL overall [10,11] and in specific domains (e.g., "physical health") [12], while others indicated levels of psychological, social, and emotional HRQOL [13] comparable to healthy peers. Interestingly, parents perceived children's HRQOL to be poorer than transplant recipients self-reported [14].…”
Section: Health-related Quality Of Life Among Pediatric Kidney Transp...mentioning
confidence: 99%